Mental Health among Orphan and Non-Orphan Adolescents (International Journal of Food and Nutritional Sciences, 2022)
Mental health is defined as a state of happiness in which each person understands his or her own protentional of handling challenges of life. A mentally healthy person can work effectively and joyfully and can make an influence on others. An orphan is a person who has lost both his parents and mostly learns to cope with the issues while experiencing life adversity. The main aim of this study is to find mental health among orphan and non-orphan adolescents in Raipur and Bilaspur. 40 orphan adolescents were selected from the different orphanages of the Raipur and Bilaspur of Chhattisgarh using a purposive sampling method, similarly, 40 non-orphan adolescents were selected from different schools. General Health Questionnaire- 28 was used to measure somatic, anxiety, social dysfunction, and depression. Both the group were found significantly different on somatic (t = 10.30; p